2014
DOI: 10.1007/s00431-014-2373-8
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent versus continuous phototherapy for the treatment of neonatal non-hemolytic moderate hyperbilirubinemia in infants more than 34 weeks of gestational age: a randomized controlled trial

Abstract: In term and late preterm infants with non-hemolytic moderate hyperbilirubinemia, intermittent phototherapy with 12 h on and 12 h off cycles is as efficacious as continuous phototherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 8 publications
3
37
0
4
Order By: Relevance
“…All neonatal units in Norway routinely allowed phototherapy to be interrupted for 30-60 minutes for breastfeeding, clinical examinations, parental visits and skin-toskin contact (Table 4). This was in accordance with studies that concluded that intermittent phototherapy was as effective as continuous phototherapy (23,24). Routinely increasing fluid supplementation during phototherapy is not indicated, as specifically stated in the national guidelines, and only one NICU continued to follow this outdated practice.…”
Section: Discussionsupporting
confidence: 92%
“…All neonatal units in Norway routinely allowed phototherapy to be interrupted for 30-60 minutes for breastfeeding, clinical examinations, parental visits and skin-toskin contact (Table 4). This was in accordance with studies that concluded that intermittent phototherapy was as effective as continuous phototherapy (23,24). Routinely increasing fluid supplementation during phototherapy is not indicated, as specifically stated in the national guidelines, and only one NICU continued to follow this outdated practice.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, in a 1975 article, 11 Dobbs and Cremer noted that intermittent phototherapy produced better results than continuous exposure. Other studies 30,34 have also suggested that, in the absence of severe haemolysis, intermittent phototherapy is at least equivalent to continuous phototherapy. In fact, a study 34 by Sachdeva and colleagues suggested that, in near-term and term infants with moderate hyperbilirubinaemia but without haemolysis, 12 h of phototherapy followed by a 12 h break is as effective as continuous phototherapy for 24 h.…”
Section: Discussionmentioning
confidence: 93%
“…14 O PMT-T apresenta também com maior frequência quadros de icterícia, 8 com indicação de uso de fototerapia. 15 Embora os quadros de hipotermia pareçam ser mais frequentes entre os PMT-T, não encontramos diferença estatística entre os grupos quanto à ocorrência de hipotermia, o que nos leva a especular ser um achado possivelmente relacionado à assistência efetuada e não à IG.…”
Section: Discussionunclassified